Seasonal breeding effects on productivity - Peacock, C.P. (International Livestock Centre for Africa, 1983)
Study report on sheep and goats production in Kenya. Data collected over a period of three years at Masai group ranch at Elangata Wuas in Kenya were examined. Data on status and progress at present on 3 adjacent newly-formed ranches included.